Could cannabinoids provide a new hope for ovarian cancer patients? - Rimanee Kaur; Farideh A. Javid (Wiley, 2023)
Abstract It is known that gynecological cancers remain a worldwide problem and as shown by the statistics, there is a need for new gynecological cancer treatments. Cannabinoids, the pharmacologically active compounds of the Cannabis sativa plant, have been used for many centuries by individuals as a symptomatic treatment to alleviate pain, nausea, vomiting, and to help stimulate appetite. Research has revealed that cannabinoids also exert anti‐cancer activity such as anti‐proliferative and pro‐apoptotic effects through a variety of mechanisms. There is significant value in the development of these compounds as anti‐cancer therapies in clinical practice as they do not produce the typical toxic side effects that exist with conventional therapies and recent clinical trials have shown their great tolerability by patients at high doses. Cannabinoids can induce psychoactive effects that could limit their progression. Therefore, non‐psychoactive cannabinoids are attracting pharmacological interest due to their inability to produce psychological effects. Recent studies have focussed on non‐psychoactive cannabinoids in ovarian cancer and have revealed promising pre‐clinical results that indicate that these compounds may have potential benefits in the treatment of these cancers. However, there are still unanswered questions and research gaps that need to be addressed. This review summarizes the current understanding of this topic and identifies the current gaps in knowledge that provide a useful direction for future work.